دور سياسات التوظيف في عصرنة الإدارة العمومية الجزائرية 2013 - 2016 - بادة, طارق (جامعة الوادي -University eloued, 2017)
تحدثت الدراسة في الفصل الأول عن الإطار المفاهيمي للتوظيف و الإدارة العمومية تناولنا فيه مفهوم التوظيف ومبادئه ومراحله وأهميته كما تطرقنا إلى مفهوم الإدارة العمومية ، تعريفها ، أهميتها ، وظائفها والأسلاك والشعب التي تنتمي إليها. إن التوظيف هو العملية التي تلبي احتياجات المنظمة من الموارد البشرية ، حيث تعتمد الإدارة العمومية في تنفيذ مهامها على أشخاص يطلق عليهم صفة موظفين تحقق من خلالهم الإدارة أهدافها ، لذلك يستلزم منها تبني عملية توظيف فعالة قائمة على إجراءات و أساليب جيدة ، يضمن لها التموين الكافي بالموارد البشرية ذات الكفاءة والمهارة المطلوبة ، فقرارات التوظيف أصبحت تشكل قرارات استراتيجية لها تأثير مباشر على مستقبل المؤسسة. أما في الفصل الثاني فقد تحدثت الدراسة عن موقع سياسات التوظيف من عصرنة الإدارة العمومية الجزائرية وتناول الأساليب والإجراءات المتخذة لتطوير الإدارة العمومية في الجزائر والإصلاحات التي جاءت في هذا المجال والمشاريع المعتمدة في عصرنة الإدارة العمومية ودور الجهات المسؤولة في ذلك ، وكيفية الإدارة الإلكترونية للموارد البشرية في الإدارات العمومية الجزائرية وما يجب أن يكون. تعتبر الإدارة الإلكترونية للموارد البشرية ﺇحدى أساليب العصرنة الإدارية التي تسد احتياجات المؤسسة من استقطاب واختيار وتوظيف لأحسن الأفراد ولوضع الرجل المناسب في المكان المناسب ، فعلى الجزائر إن أرادت تطوير إداراتها العمومية أن تعتمد على تكنولوجيا الإعلام لأنها من الأدوات التي تساعد الإدارة في بناء نظم معلومات The study discussed the conceptual framework of employment and public administration in which we discussed the concept of employment, its principles, stages, and importance. We also discussed the concept of public administration, its definition, its importance, its functions, its wiring and the people it belongs to. Recruitment is the process that meets the human resources needs of the Organization. The public administration is responsible for the implementation of its tasks by people who are referred to as employees through which the management achieves its objectives. Therefore, it is necessary to adopt an effective recruitment process based on good procedures and procedures. With the required skills and skills, employment decisions have become strategic decisions that have a direct impact on the future of the institution. In the second chapter, the study discussed the location of employment policies from the modernization of the Algerian public administration and the methods and procedures taken for the development of public administration in Algeria, the reforms that came in this field and the projects adopted in modernizing the public administration and the role of those responsible, And what should be. The electronic management of human resources is one of the methods of administrative modernization that meets the needs of the organization to attract, select and employ the best people and to put the right man in the right place. If Algeria wants to develop its public administrations to rely on information technology because it is a tool that helps management in building information systems and operations Hire faster, less effort and cost
سياسة عامة
Keywords: التوظيف ، سياسات التوظيف ، عصرنة الإدارة ، الإدارة العمومية ، الوظيف العمومي ، الموارد البشرية ، الأدارة الإلكترونية ، الموظف ، مسابقات التوظيف ، الإستقطاب ، الإختيار ، التعيين ، الترقية; Recruitment, recruitment policies, management modernization, public administration, public service, human resources, e-management, employee, recruitment competitions, polarization, selection, appointment, promotion